Barriers and Opportunities for the Development of Small Entrepreneurship in the Rural Areas of Poland and Lithuania in the Opinions of Economists (Research Bulletins of the Faculty of Economic Sciences, 2018)
The study addressed a problem of barriers and opportunities for entrepreneurship development in Poland and Lithuania. Symmetrical research in the form of an interview was conducted among 50 scientific employees - economists from the Universities of Agriculture in Krakow and Kaunas. The results of the studies have shown that the main barriers to the development of enterprises in Poland concern very high pension contributions, that are paid by the entrepreneurs, as well as a complicated VAT payment system. Moreover, the respondents from Lithuania pointed to poor economic conditions in rural areas, and related to them: unemployment and poverty of some residents of the countryside. On the other hand, in Poland big prospects for the development of entrepreneurship were seen in the opening of eastern markets and in the support of small businesses with EU funds. In Lithuania, such chances were indicated in professional consultancy and the use of EU assistance funds.
Keywords: small entrepreneurship, barriers and opportunities for entrepreneurship, comparing the conditions of Poland and Lithuania